Utilization of Acacia mangium as supplement for growing sheep - Clavero, Tyrone; Razz, Rosa (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Confined West African sheep were offered chopped sun-dried Acacia mangium leaves at levels of 0, 20, 40 and 60% in a diet with chopped hay of Brachiaria humidicola over a period of 21 days to evaluate intake and nitrogen metabolism. The experimental design was a randomized block with four replications. Dry matter intake (DMI) was affected by Acacia feeding (P < 0.05). DMI increased with increasing level of Acacia in the diets. The corresponding DMI values were 2.2, 2.8, 3.5 and 4.1 kg per 100 kg LW. Acacia mangium supplementation had a highly significant (P < 0.01) effect on nitrogen utilization by sheep. Nitrogen intake and percent of nitrogen apparently retained rose with increasing levels of Acacia. Nitrogen retention was negative for unsupplemented sheep but positive for Acacia-mixed diets.